A Analysis of Data Center Information System Feasibility by using TELOS method (Case Study: Department of Information Systems UIN Suska Riau) - Rizki Illahi, Rakhul (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2023)
This research uses the TELOS approach to assess the risks and feasibility of developing current systems as part of the information systems study program. The examination begins with technical feasibility, followed by economic feasibility, legal feasibility, operational feasibility, and time-frame feasibility. Observational and interview-based methods for data collecting. The research's findings demonstrate that the development of the data centre information system is ELIGABLE.